Increased osteoblast GαS level determines bone response to hyperparathyroidism in female mice. Issue 1 (31st May 2022) - Zhang, Lucia; Lee, Kathy K; Sugamori, Kim S; Grynpas, Marc D; Mitchell, Jane
Abstract : GS, the stimulatory heterotrimeric G protein, is an essential regulator of osteogenesis and bone turnover. To determine if increasing GαS in osteoblasts alters bone responses to hyperparathyroidism, we used a transgenic mouse line overexpressing GαS in osteoblasts (GS -Tg mice). Primary osteoblasts from GS -Tg mice showed increased basal and parathyroid hormone (PTH)-stimulated cAMP and greater responses to PTH than cells from WT mice. Skeletal responses to 2-week continuous PTH administration (cPTH) in female mice resulted in trabecular bone loss in WT mice but 74% and 34% increase in trabecular bone mass in long bones and vertebrae, respectively, in GS -Tg mice. Vertebral biomechanical strength was compromised by cPTH treatment in WT mice but not in GS -Tg. Increased peritrabecular fibrosis was greatly increased by cPTH in Gs -Tg compared to WT mice and corresponded with greater increases in Wnt pathway proteins in trabecular bone. Cortical bone responded negatively to cPTH in WT and Gs -Tg mice with large increases in porosity, decreased cortical thickness and compromised biomechanical properties. These results demonstrate that hyperparathyroidism can increase trabecular bone when GS expression and cAMP stimulation in osteoblasts are increased but this is not the case in cortical bone where increased GS expression exacerbates cortical bone loss.